THE TRANSACTION OFDROPSHIPPING ON THE VIEWs OF ISLAMIC ECONOMICS LAW - Cahyo, Eko Nur (Ijtihad : Jurnal Hukum dan Ekonomi Islam, 2019)
This study tries to analyzethe correct sellingand purchasing transactions whichcomply with law ofIslamiceconomic and compared with the dropshipping mechanismon online business. This study was found that thetransaction by using dropshipping mechanism afterreviewing from the aspect of pillarsofselling and purchasingaccording to syariah economic law had not fulfilled therequirements, specially in terms of ma’qud alaih (objector goods transacted) so it can be concluded through twoopinions, that is dropshipping which has prohibited was thepractice of selling and purchasing under the usual dropshipmechanism, and using a salam contract scheme, while theallowable dropshipping was a dropshipping mechanism which used an intermediary or samsarah scheme, and arepresentative or wakalah scheme.